From individual to relational strategies: Transforming a manual-based psycho-educational course at school. (May 2013) - Wickström, Anette
The present article focuses on 13-year-old girls' meaning-making processes during participation in a manual-based psycho-educational course at school. Drawing on childhood studies and ethnographic investigations of subjectivity, the author explores how the course is realized in practice. The analysis, based on video-recordings of 13 classes, shows that the girls and the teachers, through collective transformation, move the focus from individual potential problems to relational issues. The results demonstrate the weakness of using manual-based educational courses, and indicate that cognitive methods for dealing with negative thoughts could be replaced by exercises designed to deal with interaction and strengthening the individual.